Induced tetraploids of ginger (Zingiber officinale Rosc.) - NAIR, K RAMACHANDRAN, P N CHANDRASEKHARAN (Journal of Spices and Aromatic Crops, 1992)
Autotetraploids were produced in a clone of ginger by treating sprouting buds on the rhizome with 0.25% colchicine solution. The tetraploid was more vigorous in growth, had larger rhizomes and high yield. Oil content of rhizomes, however, was lower in the tetraploid than in the original diploid cultivar.